Transformation of History Education Based on Local Wisdom to Foster Historical Awareness in Generation Z - Agus Mursidi; Dewa Made Alit (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This research aims to analyze the transformation of history learning based on local wisdom in fostering historical awareness in generation Z at MA Matik Al Uswah Banyuwangi. The background of this research is based on the need to strengthen students' historical identity and character through a contextual, meaningful, and local culture-based approach in the midst of strong digitalization and globalization currents. The methodology used is a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation studies. The research informants consisted of a history teacher (Yumna), a school principal (Ustadz Oky), and a grade XII student (Fahat Indra Tanaya and Anugrah Zulkarnaik Saputra). The results show that the integration of local wisdom in history learning makes a significant contribution to improving student understanding, emotional engagement, and character. Digital media such as documentary videos, project based learning, and virtual tours of local historical sites have proven effective in building connections between teaching materials and students' real lives. Another important finding is the increase in critical thinking skills and appreciation of local cultural values. This finding shows that history learning innovations based on local wisdom and supported by digital technology are able to become a transformative and adaptive learning model to the characteristics of generation Z. This study recommends the expansion of this model to other educational units to strengthen students' character education and historical literacy in a sustainable manner in the era of disruption. Ultimately, this research not only contributes to strengthening character education and historical literacy but also offers a scalable framework for educational transformation in the era of disruption, ensuring history learning remains relevant, engaging, and culturally grounded.